1982
DOI: 10.1111/j.1432-1033.1982.tb06692.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Tryptophanyl-tRNA Synthetase with the Triazine Dye Brown MX-5BR

Abstract: Brown MX‐5 BR specifically and irreversibly inactivates tryptophanyl‐tRNA synthetase from Bacillus stearo‐thermophilus at pH 8.5. The enzyme is protected from inactivation by the substrates tryptophan and ATP and to lesser extents by ADP, AMP, the product inorganic pyrophosphate and other nucleotides such as GTP. The Kd of the pure reactive dye for the enzyme uah measured to be 6.7 × 10−5 M. The Km values of the two substrates tryptophan and MgATP were found to be 1 × 10−5 M and 5×10−5 M respectively. The amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
5

Year Published

1984
1984
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
5
0
5
Order By: Relevance
“…80%) of the dye purified by t.l.c. The inactivating ability of pure Brown MX-5BR with respect to WTS has been reported previously (McArdell et al, 1982). Fig.…”
Section: Inhibitor Studiessupporting
confidence: 65%
See 1 more Smart Citation
“…80%) of the dye purified by t.l.c. The inactivating ability of pure Brown MX-5BR with respect to WTS has been reported previously (McArdell et al, 1982). Fig.…”
Section: Inhibitor Studiessupporting
confidence: 65%
“…3 shows that tyrosine does not protect YTS from inactivation by Brown MX-5BR, whereas ATP confers significant protection to this enzyme. The inhibition constant of aminated Brown MX-5BR with respect to WTS reported previously (McArdell et al, 1982) showed that the dye has a high affinity for the tryptophyladenylate-binding site. The inhibition of YTS by aminated Brown MX-5BR exhibited mixed kinetics and a low affinity for the tyrosine-binding site.…”
Section: Inhibitor Studiesmentioning
confidence: 73%
“…where kobs is the observed rate of enzyme inactivation at a given concentration of the dye, D, k+2 is the maximum rate of inactivation (min-1) and Kd is the apparent dissociation constant, k-,/k+1, of the enzymedye complex (Kitz & Wilson, 1962;Clonis & Lowe, 1980;Witt & Roskoski, 1980;McArdell et al, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…The accumulated evidence indicates that the polysulphonated aromatic chromophores of the triazine dyes mimic naturally occurring heterocyclic biological molecules such as adenosine phosphates, NAD+, NADP+, acetyl-CoA, folate and flavins (Lowe et al,198 la; Edwards & Woody, 1979;Johnson & Stevenson, 1980;Small et al, 1981;Clonis et al, 1981). The dyes do not bind solely to proteins with a 'dinucleotide fold', as originally suggested (Thompson et al, 1975); for example the elution characteristics of aminoacyl-tRNA synthetases from triazine dye affinity-chromatography columns indicate that some dyes can mimic amino acids and others the tRNA substrates McArdell et al, 1982).…”
Section: Introductionmentioning
confidence: 92%
“…The ability of reactive chlorotriazine dyes to mimic the binding of biological ligands has led to their exploitation as effective irreversible affinity labels, particularly for nucleotidedependent enzymes such as dehydrogenases [lo, 17, 181, aminoacyl-tRNA synthetases [19] and kinases [lo, 15, 201. More recent studies have shown that horse liver alcohol dehydrogenase is irreversibly inactivated by a dichlorotriazinyl analogue of Cibacron blue F3G-A, Procion blue MX-R, and that subsequent isolation of a labelled peptide has shown that the dye is attached to the thiol side chain of Cys-174 in the catalytic domain of the enzyme [IS]. In the present study, the ability of a number of analogues of Procion red H-8BN to inactive carboxypeptidase G-2 in the presence and absence of metal ions was investigated in order to establish a suitable affinity label for this enzyme.…”
mentioning
confidence: 99%